THE DEVELOPMENT OF A GENE POOL OF WHEAT AND TRITICALE AND ITS USE IN BREEDING - P. I. Stepochkin (Вавиловский журнал генетики и селекции)
The results of the work on the development of the gene pool of Siberian spring common wheat and spring and winter triticale are reported. Collections of traits and genes and working collections of these cereals are described. The gene pool includes almost all landraces of Siberian origin. All accessions are registered in the certificate database and have numbers of the Siberian Institute of Plant Industry and Breeding. Atypical forms collected from heterogeneous populations also have their accession numbers. In addition, a collection of spontaneous spring mutants isolated from populations of winter crops is being developed. Twenty two spring common wheat varieties and two winter triticale varieties have been created on the base of the Siberian gene pool developed at the Institute.